GREENHOUSE GAS EMISSIONS REDUCTION DUE TO ANAEROBIC DIGESTION TECHNOLOGY IMPLEMENTATION BY THE EXAMPLE OF LENINGRAD REGION POULTRY FARM - E S Klochkova; M D Kharlamova (RUDN Journal of Ecology and Life Safety, 2015)
The article presents the assessment of greenhouse gases emissions reductions from manure management in case anaerobic digestion technology is used for organic wastes processing. The research was made under IPCC (Intergovernmental Panel on Climate Change) Guidelines for National Greenhouse Gas Inventories’ methodology. ‘Sinyavinskaya’ poultry farm located in Leningrad region was chosen as an object of study. The analysis resulted in calculation of greenhouse gas emissions from manure management and comparison of emissions from combustion of different types of fuel